Report of meeting of I.F.T.U. General Council and L.S.I. Bureau held in Paris on Friday & Saturday, 4 & 5 December, 1936. - Internation Federation of Trade Unions ; Labour and Socialist International
1936-12-18 015b_0028_001 292/946/15b/28(i)